Systemic nitric oxide metabolites and the chance of pre-diabetes regression to normoglycemia: A 9-year cohort study - Zahra Bahadoran; Parvin Mirmiran; Fereidoun Azizi; Asghar Ghasemi (BioImpacts)
Introduction: We aimed to track longitudinal changes of glycemic status in subjects with pre-diabetes (Pre-DM) in relation to their baseline levels of systemic nitric oxide (NO) production [i.e., measured as serum NO metabolites (NOx), crude and body weight (BW)-adjusted NOx to creatinine ratio (NOx-to-Cr)] over 9 years. Methods: This cohort study included 541 middle-aged Iranian men and women with Pre-DM, recruited in 2006-2008 and followed up to 2015-2017. The colorimetric Griess method was used to measure serum NOx concentration. Multinomial logistic regression analyses estimated the odds ratios (OR) of Pre-DM regression and progression across tertiles (tertile 3 vs. tertile 1 and tertile 2) of serum NOx, crude, and BW-adjusted NOx-to-Cr ratio. Results: Participants who regressed to normoglycemia (NG) had a higher BW-adjusted NOx-to-Cr ratio than those who developed type 2 diabetes (T2D) or those who remained Pre-DM (0.52±0.34 vs. 0.43±0.25 and 0.48±0.29, P=0.023). Higher BW-adjusted NOx-to-Cr increased chance of returning to NG (OR=2.05, 95% CI= 0.98-4.32, P=0.058) and decreased levels of 2h-serum glucose over time (Ptime×group=0.025), as well as the decreased overall mean of fasting (106, 95% CI=103-109 vs. 110, 95% CI=108-112 mg/dL, P=0.008) and 2h-serum glucose (153, 95% CI=146-159 vs. 163, 95% CI=158-168 mg/dL, P=0.018). Conclusion: A higher endogenous NO production (i.e., indirectly measured by BW- and Cr-adjusted serum NOx concentration) in Pre-DM subjects is associated with the chance of returning to NG.